A method for producing 1j50 alloy based on metal injection molding

CN122913501APending Publication Date: 2026-10-16HUNAN FEDEC MSTAR TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611358283.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

传统用金属注射成型制备1J50合金常采用由羰基法生产的单元质羰基铁粉和羰基镍粉按材质质量百分比组分混合得到预合金粉末,虽然羰基法生产的羰基铁粉和镍粉的粉末粒径细、球形度好,但由于其粉末粒径分布范围窄、振实密度低导致最终烧结密度低

Benefits of technology

(1)本发明以单质块体为原料由雾化法制备雾化合金粉末,然后将纳米羰基镍粉加入到雾化合金粉末中进行混合球磨扩散,实现羰基镍粉对雾化合金粉末的包覆保护,从而获得扩散合金粉末。在以硝酸作为催化剂的催化脱脂过程中能够避免硝酸与铁的化学反应与腐蚀。结合复配粘结剂的共同作用,由金属注射成型制备的1J50合金具有较高的烧结密度,同时获得良好的力学性能,具有广阔的市场前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the technical field of steel material, and particularly relates to a method for preparing 1J50 alloy based on metal injection molding. The 1J50 alloy has the following mass percentage components: C<=0.03%, Ni=49.0-51.0%, Si=0.25-0.30%, Mn=0.40-0.60%, and the balance is iron and inevitable impurities. In the present application, the elemental bulk is used as raw material to prepare atomized alloy powder by atomization method, then nano nickel carbonyl powder is added into the atomized alloy powder for mixing, ball milling and diffusion, so as to realize the coating protection of the nickel carbonyl powder on the atomized alloy powder, thereby obtaining diffusion alloy powder. In the catalytic degreasing process with nitric acid as catalyst, the chemical reaction and corrosion of nitric acid and iron can be avoided. Combined with the joint action of the compounded binder, the 1J50 alloy prepared by metal injection molding has high sintering density and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of steel material technology, specifically relating to a method for preparing 1J50 alloy based on metal injection molding. Background Technology

[0002] Metal injection molding (MIM) is a near-shaped metal parts manufacturing process that introduces modern plastic molding technology into the field of powder metallurgy. It solves the shortcomings of traditional powder metallurgy processes, such as difficulty in manufacturing complex parts and performance limitations. Generally, alloy materials that can be made into powder can be processed using metal injection molding. The excellent process characteristics of metal injection molding make it suitable for producing metal parts with complex shapes, miniature size, large batches, high precision, and special performance requirements. The process steps of metal injection molding include: (1) metal powder preparation, (2) mixing and kneading the metal powder with a binder to form a feedstock, (3) injection molding, (4) removing the binder, and (5) sintering to obtain a densified alloy.

[0003] 1J50 alloy, with its excellent physical properties, is widely used in the production of instruments and meters, watch components, outdoor mobile communication base station antenna receiver parts, wireless headphones, and laser printer parts. Traditionally, 1J50 alloy is prepared by metal injection molding using a pre-alloyed powder obtained by mixing unit carbonyl iron powder and carbonyl nickel powder produced by the carbonyl method according to the material mass percentage. Although the carbonyl iron and nickel powders produced by the carbonyl method have fine particle sizes and good sphericity, their narrow particle size distribution and low tap density result in a low final sintering density. Simultaneously, using this pre-alloyed powder to prepare a plastic-based feedstock mainly composed of polyoxymethylene, during the catalytic degreasing process using nitric acid as a catalyst, the cracking reaction between nitric acid and polyoxymethylene starts from the surface of the preform and forms channels that penetrate deep into the core of the preform. However, due to the fine particle size of carbonyl iron powder and carbonyl nickel powder and the small gap between the powder particles, the speed at which nitric acid penetrates into the core of the preform is slow. The preform is in a nitric acid atmosphere for a long time, and the chemical reaction and corrosion between nitric acid and iron elements form crystals mainly composed of ferrous nitrate that adhere to the surface of the preform and block its channels, resulting in the technical problem that the polyoxymethylene in the core of the preform is difficult to crack.

[0004] Therefore, the key research direction is to find a way to prepare 1J50 alloy by metal injection molding, avoid the chemical reaction and corrosion of nitric acid and iron and improve the degreasing rate in the catalytic degreasing process with nitric acid as a catalyst, and obtain high sintering density and good mechanical properties. Summary of the Invention

[0005] To address the deficiencies and shortcomings in the aforementioned background technology, this invention provides a method for preparing 1J50 based on metal injection molding. This invention uses a single-element bulk material as raw material to prepare atomized alloy powder via atomization. Then, nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion, achieving a coating and protection of the atomized alloy powder by the carbonyl nickel powder, thereby obtaining diffused alloy powder. During the catalytic degreasing process using nitric acid as a catalyst, the chemical reaction and corrosion between nitric acid and iron can be avoided. Combined with the synergistic effect of a compound binder, the 1J50 alloy prepared by metal injection molding exhibits high sintering density and good mechanical properties. Therefore, the technical solution proposed by this invention is as follows: A method for preparing 1J50 alloy based on metal injection molding, wherein the 1J50 alloy comprises, by weight percentage, C ≤ 0.03%, Ni = 49.0-51.0%, Si = 0.25-0.30%, Mn = 0.40-0.60%, with the balance being iron and unavoidable impurities. The method includes the following steps: S1: Atomized alloy powder is prepared by atomization using Ni, Si, Mn and Fe elemental bulk materials as raw materials; S2: Nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling and diffusion, and then vacuum dried to obtain diffusion alloy powder; S3: Mix the diffusion alloy powder with the binder and knead it thoroughly. After kneading until uniform, the mixture is granulated by a pelletizer to obtain granular feed. S4: The granular feed is poured into the hopper of the injection molding machine, and after plasticization, it is injected into the closed mold cavity to obtain the molded blank; S5: Catalytically degrease the formed blank to obtain a degreased blank; S6: The degreased blank is sintered to obtain a high-density, high-strength 1J50 alloy.

[0006] This invention uses elemental bulk materials to prepare atomized alloy powder via atomization. Then, nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion, achieving a coating and protection of the atomized alloy powder by the carbonyl nickel powder. This process yields diffusion alloy powder. The catalytic degreasing process using nitric acid as a catalyst avoids the chemical reaction and corrosion between nitric acid and iron. Combined with the effects of a compound binder, the 1J50 alloy prepared by metal injection molding exhibits high sintering density and excellent mechanical properties, demonstrating broad market prospects.

[0007] As a preferred technical solution of the present invention, the atomized alloy powder in step S1 comprises C≤0.03%, Ni=40.0-42.0%, Si=0.30-0.35%, Mn=0.50-0.70%, with the balance being iron and unavoidable impurities; As a preferred technical solution of the present invention, the particle size D50 of the atomized alloy powder in step S1 is 8-10 μm; As a preferred embodiment of the present invention, in step S2, the nano-carbonyl nickel powder has a particle size D50 of 80-100 nm and a tap density of 0.30-0.50 g / cm³. This invention utilizes the high specific surface area and activity of nano-carbonyl nickel powder to act as crystal nuclei during alloy solidification, inhibiting grain growth and refining grains. This fine-grain strengthening effect improves the mechanical properties of the alloy. At the same time, the nano-carbonyl nickel powder has unique micromorphologies such as three-dimensional chain and dendritic structures, which are beneficial for forming a uniform and dense structure with the 1J50 alloy matrix during sintering, reducing lattice distortion and defects, thereby improving the alloy density.

[0008] As a preferred technical solution of the present invention, the mass ratio of nano-carbonyl nickel powder to atomized alloy powder in step S2 is 15:85. As a preferred technical solution of the present invention, the ball milling process in step S2 is as follows: the ball milling medium is anhydrous ethanol, the diameter of the steel ball is 6 mm, the ball milling time is 20-24 hours, and the rotation speed is 100-150 r / min. As a preferred technical solution of the present invention, the vacuum drying process in step S2 is as follows: vacuum degree 0.092~0.098Pa, drying temperature 110-140℃, drying time 4-5 hours; This invention involves ball milling nano-carbonyl nickel powder with atomized alloy powder. Under the force of the steel ball, the powder morphology is spheroidized, and the tap density is improved, which is beneficial for increasing the density of the alloy and obtaining good mechanical properties. Simultaneously, the frictional force between the powders continuously increases under the force of the steel ball, leading to diffusion between metal elements and forming a nickel-rich adhesion layer on the surface of the atomized alloy powder. This enhances interfacial bonding during sintering, accelerates liquid phase flow, and facilitates grain growth as it moves outwards towards grain boundaries to fill intergranular voids, thereby improving the alloy's density and strength.

[0009] As a preferred embodiment of the present invention, the adhesive components in step S3 by mass percentage include: 80% polyoxymethylene, 5% polyethylene, 5% polypropylene, 3% ethylene-vinyl acetate copolymer, and 2% sodium alginate; This invention uses polyoxymethylene (POM), polyethylene (PE), polypropylene (PP), ethylene-vinyl acetate copolymer (EVA), and sodium alginate as compound binder components. POM possesses high rigidity and adhesion, enhancing particle mechanical interlocking and significantly increasing green body density. PE, PP, and EVA have high flowability and low melting points, filling inter-particle voids during powder mixing and injection molding, resulting in a denser green body structure. Sodium alginate forms hydrogen or ionic bonds on the particle surface through hydroxyl and carboxyl groups, increasing interfacial bonding and reducing particle slippage during injection molding, leading to a more uniform and dense green body structure. The decomposition products of sodium alginate act as heterogeneous nucleating agents, inhibiting grain growth and refining grains. This grain refinement effect improves the mechanical properties of the alloy, and through its synergistic effect with POM, PE, PP, and EVA, it enhances the alloy's density and strength.

[0010] As a preferred embodiment of the present invention, the binder content in step S3 is 9% of the mass percentage of the diffusion alloy powder; As a preferred technical solution of the present invention, the mixing process conditions in step S3 are: mixing temperature 190-210℃, duration 1-2 hours, and rotation speed 100-150r / min; As a preferred technical solution of the present invention, the injection molding process conditions in step S4 are as follows: injection pressure 90-100 Bar, injection speed 10-30 cm³ / s, injection time 1-5 seconds, holding pressure 80-90 Bar, holding speed 10-30 cm³ / s, holding time 1-5 seconds, nozzle temperature 190-195℃, first stage temperature 180-185℃, second stage temperature 170-175℃, third stage temperature 160-165℃, and mold temperature 120-140℃.

[0011] As a preferred technical solution of the present invention, the catalytic degreasing process conditions in step S5 are as follows: using 98% fuming nitric acid as a catalyst and nitrogen as a protective gas with a flow rate of 40-50 L / min, catalytic degreasing temperature of 110-140℃, nitric acid feed rate of 2-3 g / min, and terminating the degreasing process when the product weight loss rate reaches 7.00%.

[0012] This invention employs a catalytic degreasing process, where all iron elements are located within the atomized alloy powder. Nano-carbonyl nickel powder is added to the atomized alloy powder and mixed and ball-milled, achieving a protective coating of the atomized alloy powder with carbonyl nickel powder. This forms a nickel-rich adhesion layer on the surface of the atomized alloy powder, thus preventing chemical reaction and corrosion between nitric acid and iron during the catalytic degreasing process using nitric acid as a catalyst. Simultaneously, the coarse particle size of the atomized alloy powder (D50 = 8-10 μm) increases the interparticle spacing, improving the catalytic degreasing rate and reducing the acid exposure time of the formed blank. This effectively reduces the risk of chemical reaction between nitric acid and iron, thereby contributing to increased density and strength of the 1J50 alloy.

[0013] As a preferred technical solution of the present invention, the sintering process conditions in step S6 are: sintering temperature 1370-1380℃, holding time 120-150 minutes, and rapid cooling to room temperature after furnace cooling to 900℃.

[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses elemental bulk material to prepare atomized alloy powder by atomization. Then, nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion, thereby achieving the coating and protection of the atomized alloy powder by the carbonyl nickel powder, thus obtaining diffused alloy powder. In the catalytic degreasing process using nitric acid as a catalyst, the chemical reaction and corrosion between nitric acid and iron can be avoided. Combined with the combined effect of the compound binder, the 1J50 alloy prepared by metal injection molding has a high sintering density and good mechanical properties, and has broad market prospects.

[0015] (2) The present invention adopts a catalytic degreasing process, in which all iron elements are located in the atomized alloy powder. Nano-carbonyl nickel powder is added to the atomized alloy powder for mixing and ball milling, so as to achieve the coating and protection of the atomized alloy powder by the carbonyl nickel powder, forming a nickel-rich adhesion layer on the surface of the atomized alloy powder. Thus, in the catalytic degreasing process with nitric acid as catalyst, the chemical reaction and corrosion between nitric acid and iron can be avoided. At the same time, the atomized alloy powder has a coarse particle size (D50=8-10μm), and the channel gap between powder particles is increased, which improves the catalytic degreasing rate. This can reduce the acid exposure time of the formed blank and effectively reduce the risk of chemical reaction between nitric acid and iron elements, thereby improving the density and strength of 1J50 alloy.

[0016] (3) In this invention, nano-carbonyl nickel powder and atomized alloy powder are mixed and ball-milled. Under the action of the steel ball, the powder morphology is spheroidized and the tap density is improved, which is beneficial to improving the density of the alloy and obtaining good mechanical properties. At the same time, the friction between the powders increases continuously under the action of the steel ball, and diffusion occurs between the metal elements, forming a nickel-rich adhesion layer on the surface of the atomized alloy powder. This is beneficial to enhance the interfacial bonding force during sintering, accelerate the liquid phase flow, and move outward to fill the gaps between grains as the grains grow, thereby improving the density and strength of the alloy.

[0017] (4) The present invention uses nano-carbonyl nickel powder with high specific surface area and activity to act as crystal nuclei during the solidification process of the alloy, inhibiting grain growth and refining grains. The mechanical properties of the alloy are improved through the fine grain strengthening effect. At the same time, nano-carbonyl nickel powder has unique micromorphology such as three-dimensional chain and dendritic structure, which is conducive to forming a uniform and dense structure with the 1J50 alloy matrix during sintering, reducing lattice distortion and defects, thereby improving the alloy density.

[0018] (5) This invention uses polyoxymethylene, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, and sodium alginate as the compound binder components. Polyoxymethylene, as a binder component, has high rigidity and adhesion, which can enhance the mechanical interlocking of particles and significantly increase the green body density. Polyethylene, polypropylene, and ethylene-vinyl acetate copolymer have high fluidity and low melting point, which can fill the gaps between particles during powder mixing and injection molding, making the green body structure more compact. Sodium alginate forms hydrogen bonds or ionic bonds on the particle surface through hydroxyl and carboxyl groups, increasing the interfacial bonding force, reducing particle slippage during injection molding, and making the green body structure more uniform and compact. The decomposition products of sodium alginate can act as heterogeneous nucleating agents, inhibiting grain growth and refining grains, improving the mechanical properties of the alloy through the grain refinement strengthening effect, and improving the density and strength of the alloy through the combined action with polyoxymethylene, polyethylene, polypropylene, and ethylene-vinyl acetate copolymer. Detailed Implementation

[0019] To facilitate understanding of the present invention, preferred embodiments will be used to describe the present invention in more detail below. Those skilled in the art should understand that the scope of protection of the present invention is not limited to the following embodiments. The raw materials, equipment, instruments and reagents used in the embodiments and comparative examples of this invention can all be purchased from the market or prepared by existing methods.

[0020] Example 1: A method for preparing 1J50 alloy based on metal injection molding, wherein the 1J50 alloy comprises, by mass percentage, C ≤ 0.03%, Ni = 49.0%, Si = 0.25%, Mn = 0.40%, with the balance being iron and unavoidable impurities. And includes the following steps: S1: Atomized alloy powder is prepared from Ni, Si, Mn, and Fe elemental bulk materials using an atomization method. The atomized alloy powder composition by mass percentage includes C ≤ 0.03%, Ni = 40.0%, Si = 0.30%, Mn = 0.50%, with the balance being iron and unavoidable impurities; the atomized alloy powder particle size D50 = 9 μm. S2: Nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion. After vacuum drying, diffused alloy powder is obtained. The nano-carbonyl nickel powder has a particle size D50 of 80 nm and a tap density of 0.50 g / cm³. The ball milling process is as follows: anhydrous ethanol as the milling medium, steel ball diameter of 6 mm, milling time of 20 hours, and rotation speed of 100 r / min. The vacuum drying process is as follows: vacuum degree of 0.092 Pa, drying temperature of 110℃, and drying time of 4 hours. S3: The diffusion alloy powder and binder are mixed and kneaded in an intensive kneading process. After uniform kneading, the mixture is granulated by a pelletizer to obtain granular feed. The binder composition by mass percentage includes: 80% polyoxymethylene, 5% polyethylene, 5% polypropylene, 3% ethylene-vinyl acetate copolymer, and 2% sodium alginate; the binder content is 9% of the diffusion alloy powder by mass; the kneading process conditions are: kneading temperature 190℃, duration 1 hour, and rotation speed 100 r / min. S4: The granular feedstock is poured into the hopper of the injection molding machine, and after plasticization, it is injected into the closed mold cavity to obtain a preform; wherein the injection molding process conditions are: injection pressure 90 Bar, injection speed 15 cm³ / s, injection time 3 seconds, holding pressure 80 Bar, holding speed 20 cm³ / s, holding time 3 seconds, nozzle temperature 190℃, first stage temperature 180℃, second stage temperature 170℃, third stage temperature 160℃, mold temperature 125℃.

[0021] S5: The formed blank is subjected to catalytic degreasing to obtain a degreased blank; wherein the catalytic degreasing process conditions are: using 98% fuming nitric acid as a catalyst and nitrogen as a protective gas with a flow rate of 40L / min, catalytic degreasing temperature of 115℃, nitric acid feed rate of 2g / min, and terminating the degreasing process when the product weight loss rate reaches 7.00%. S6: The degreased billet is sintered to obtain a high-density, high-strength 1J50 alloy. The sintering process conditions are: sintering temperature 1370℃, holding time 120 minutes, furnace cooling to 900℃ and then rapid cooling to room temperature.

[0022] Example 2: A method for preparing 1J50 alloy based on metal injection molding, wherein the 1J50 alloy comprises, by mass percentage, C ≤ 0.03%, Ni = 50.0%, Si = 0.27%, Mn = 0.50%, with the balance being iron and unavoidable impurities, and includes the following steps: S1: Atomized alloy powder is prepared from Ni, Si, Mn, and Fe elemental bulk materials using an atomization method. The atomized alloy powder composition by mass percentage includes C ≤ 0.03%, Ni = 41.0%, Si = 0.32%, Mn = 0.60%, with the balance being iron and unavoidable impurities; the atomized alloy powder particle size D50 = 9 μm. S2: Nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion. After vacuum drying, diffused alloy powder is obtained. The nano-carbonyl nickel powder has a particle size D50 of 90 nm and a tap density of 0.40 g / cm³. The ball milling process is as follows: anhydrous ethanol as the milling medium, steel ball diameter of 6 mm, milling time of 22 hours, and rotation speed of 120 r / min. The vacuum drying process is as follows: vacuum degree of 0.094 Pa, drying temperature of 120℃, and drying time of 4.5 hours. S3: The diffusion alloy powder and binder are mixed and kneaded in an intensive kneading process. After uniform kneading, the mixture is granulated by a pelletizer to obtain granular feed. The binder composition by mass percentage includes: 80% polyoxymethylene, 5% polyethylene, 5% polypropylene, 3% ethylene-vinyl acetate copolymer, and 2% sodium alginate; the binder content is 9% of the diffusion alloy powder by mass; the kneading process conditions are: kneading temperature 200℃, duration 1.5 hours, and rotation speed 120 r / min. S4: The granular feedstock is poured into the hopper of the injection molding machine, and after plasticization, it is injected into the closed mold cavity to obtain a preform; wherein the injection molding process conditions are: injection pressure 95 Bar, injection speed 20 cm³ / s, injection time 3 seconds, holding pressure 85 Bar, holding speed 25 cm³ / s, holding time 3 seconds, nozzle temperature 195℃, first stage temperature 185℃, second stage temperature 175℃, third stage temperature 165℃, mold temperature 130℃.

[0023] S5: The formed blank is subjected to catalytic degreasing to obtain a degreased blank; wherein the catalytic degreasing process conditions are: using 98% fuming nitric acid as a catalyst and nitrogen as a protective gas with a flow rate of 45L / min, catalytic degreasing temperature of 125℃, nitric acid feed rate of 2.5g / min, and terminating the degreasing process when the product weight loss rate reaches 7.00%; S6: The degreased billet is sintered to obtain a high-density, high-strength 1J50 alloy. The sintering process conditions are: sintering temperature 1375℃, holding time 135 minutes, furnace cooling to 900℃ and then rapid cooling to room temperature.

[0024] Example 3: A method for preparing 1J50 alloy based on metal injection molding, wherein the 1J50 alloy comprises, by mass percentage, C ≤ 0.03%, Ni = 51.0%, Si = 0.30%, Mn = 0.60%, with the balance being iron and unavoidable impurities, and includes the following steps: S1: Atomized alloy powder is prepared from Ni, Si, Mn, and Fe elemental bulk materials using an atomization method. The atomized alloy powder composition by mass percentage includes C ≤ 0.03%, Ni = 42.0%, Si = 0.35%, Mn = 0.70%, with the balance being iron and unavoidable impurities; the atomized alloy powder particle size D50 = 9 μm. S2: Nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion. After vacuum drying, diffused alloy powder is obtained. The nano-carbonyl nickel powder has a particle size D50 of 100 nm and a tap density of 0.30 g / cm³. The ball milling process is as follows: anhydrous ethanol as the milling medium, steel ball diameter of 6 mm, milling time of 24 hours, and rotation speed of 150 r / min. The vacuum drying process is as follows: vacuum degree of 0.098 Pa, drying temperature of 130℃, and drying time of 5 hours. S3: The diffusion alloy powder and binder are mixed and kneaded in an intensive mixing process. After uniform mixing, the mixture is granulated by a pelletizer to obtain granular feed. The binder composition by mass percentage includes: 80% polyoxymethylene, 5% polyethylene, 5% polypropylene, 3% ethylene-vinyl acetate copolymer, and 2% sodium alginate; the binder content is 9% of the diffusion alloy powder by mass; the mixing process conditions are: mixing temperature 210℃, duration 2 hours, and rotation speed 150 r / min. S4: The granular feedstock is poured into the hopper of the injection molding machine, and after plasticization, it is injected into the closed mold cavity to obtain a preform; wherein the injection molding process conditions are: injection pressure 100 Bar, injection speed 25 cm³ / s, injection time 3 seconds, holding pressure 90 Bar, holding speed 25 cm³ / s, holding time 3 seconds, nozzle temperature 195℃, first stage temperature 185℃, second stage temperature 175℃, third stage temperature 165℃, mold temperature 125℃.

[0025] S5: The formed blank is subjected to catalytic degreasing to obtain a degreased blank; wherein the catalytic degreasing process conditions are: using 98% fuming nitric acid as a catalyst and nitrogen as a protective gas with a flow rate of 50L / min, catalytic degreasing temperature of 130℃, nitric acid feed rate of 3g / min, and terminating the degreasing process when the product weight loss rate reaches 7.00%. S6: The degreased billet is sintered to obtain a high-density, high-strength 1J50 alloy. The sintering process conditions are: sintering temperature 1380℃, holding time 150 minutes, furnace cooling to 900℃ and then rapid cooling to room temperature.

[0026] Comparative Example 1: Compared to Example 1, this comparative example directly uses atomized alloy powder and binder mixed and kneaded. The 1J50 alloy prepared in this comparative example has the following composition by mass percentage: C ≤ 0.03%, Ni = 50.0%, Si = 0.27%, Mn = 0.50%, with the balance being iron and unavoidable impurities.

[0027] Comparative Example 2: Compared to Example 1, this comparative example did not involve ball milling after mixing the atomized alloy powder with nano-carbonyl nickel powder. The 1J50 alloy prepared in this comparative example had the following composition by mass percentage: C ≤ 0.03%, Ni = 50.0%, Si = 0.27%, Mn = 0.50%, with the balance being iron and unavoidable impurities.

[0028] Comparative Example 3: Compared to Example 1, the atomized alloy powder used in this comparative example has a particle size of D50 = 4 μm. The 1J50 alloy prepared in this comparative example has the following composition by mass percentage: C ≤ 0.03%, Ni = 50.0%, Si = 0.27%, Mn = 0.50%, with the balance being iron and unavoidable impurities.

[0029] Comparative Example 4: Compared to Example 1, this comparative example uses carbonyl nickel powder instead of nano-carbonyl nickel powder (powder particle size D50 = 12 μm). The 1J50 alloy prepared in this comparative example has the following mass percentage composition: C ≤ 0.03%, Ni = 50.0%, Si = 0.27%, Mn = 0.50%, with the balance being iron and unavoidable impurities.

[0030] Comparative Example 5: Compared to Example 1, this comparative example uses polyoxymethylene instead of the compound binder component. The 1J50 alloy prepared in this comparative example has the following composition by mass percentage: C ≤ 0.03%, Ni = 50.0%, Si = 0.27%, Mn = 0.50%, with the balance being iron and unavoidable impurities.

[0031] The sintering density test shall be conducted in accordance with the requirements of "ISO 3369:2006 Method for Determination of Density of Dense Sintered Metallic Materials and Hard Alloys"; Mechanical property testing shall be conducted in accordance with the requirements of GB / T 228.1-2021 Metallic materials, tensile testing—Part 1: Test at room temperature; The performance data of the 1J50 alloys prepared in the examples and comparative examples are shown in the table below:

[0032] As shown in the table above, this invention uses elemental bulk materials to prepare atomized alloy powder via atomization. Then, nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling, and diffusion, achieving a coating and protection of the atomized alloy powder by the carbonyl nickel powder, thereby obtaining diffused alloy powder. During the catalytic degreasing process using nitric acid as a catalyst, the chemical reaction and corrosion between nitric acid and iron can be avoided. Combined with the combined effect of the compound binder, the 1J50 alloy prepared by metal injection molding exhibits high sintering density and good mechanical properties (see Examples 1-3).

[0033] Compared with Example 1, Comparative Example 1 lacks the refining effect of nano-carbonyl nickel powder, resulting in a decrease in density and strength; compared with Example 1, Comparative Example 2 lacks the ball milling diffusion effect, resulting in a decrease in density and strength; compared with Example 1, Comparative Example 3 has fine atomized alloy powder and low tap density, resulting in a decrease in density and strength; compared with Example 1, Comparative Example 4 has coarse carbonyl nickel powder particle size and reduced sintering activity, resulting in a decrease in density and strength; compared with Example 1, Comparative Example 5 lacks the combined effect of the compound binder, resulting in a decrease in density and strength.

Claims

1. A method for preparing 1J50 alloy based on metal injection molding, wherein the 1J50 alloy comprises, by mass percentage, C ≤ 0.03%, Ni = 49.0-51.0%, Si = 0.25-0.30%, Mn = 0.40-0.60%, with the balance being iron and unavoidable impurities; characterized in that, And includes the following steps: S1: Atomized alloy powder is prepared by atomization using Ni, Si, Mn and Fe elemental bulk materials as raw materials; S2: Nano-carbonyl nickel powder is added to the atomized alloy powder for mixing, ball milling and diffusion, and then vacuum dried to obtain diffusion alloy powder; S3: Mix the diffusion alloy powder with the binder and knead it thoroughly. After kneading until uniform, the mixture is granulated by a pelletizer to obtain granular feed. S4: The granular feed is poured into the hopper of the injection molding machine, and after plasticization, it is injected into the closed mold cavity to obtain the molded blank; S5: Catalytically degrease the formed blank to obtain a degreased blank; S6: The degreased blank is sintered to obtain a high-density, high-strength 1J50 alloy.

2. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The atomized alloy powder in step S1 comprises, by mass percentage, C ≤ 0.03%, Ni = 40.0-42.0%, Si = 0.30-0.35%, Mn = 0.50-0.70%, with the balance being iron and unavoidable impurities.

3. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, In step S1, the particle size of the atomized alloy powder is D50 = 8-10 μm.

4. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, In step S2, the nano-carbonyl nickel powder has a particle size D50 of 80-100 nm and a tap density of 0.30-0.50 g / cm³.

5. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, In step S2, the mass ratio of nano-carbonyl nickel powder to atomized alloy powder is 15:

85.

6. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The ball milling process in step S2 is as follows: the ball milling medium is anhydrous ethanol, the diameter of the steel ball is 6 mm, the ball milling time is 20-24 hours, and the rotation speed is 100-150 r / min.

7. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The vacuum drying process in step S2 is as follows: vacuum degree 0.092~0.098 Pa, drying temperature 110-140℃, drying time 4-5 hours.

8. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The adhesive components in step S3 by weight percentage include: 80% polyoxymethylene, 5% polyethylene, 5% polypropylene, 3% ethylene-vinyl acetate copolymer, and 2% sodium alginate.

9. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, In step S3, the binder content is 9% of the mass percentage of the diffusion alloy powder.

10. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The mixing process conditions in step S3 are: mixing temperature 190-210℃, duration 1-2 hours, and rotation speed 100-150 r / min.

11. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The injection molding process conditions in step S4 are as follows: injection pressure 90-100 Bar, injection speed 10-30 cm³ / s, injection time 1-5 seconds, holding pressure 80-90 Bar, holding speed 10-30 cm³ / s, holding time 1-5 seconds, nozzle temperature 190-195℃, first stage temperature 180-185℃, second stage temperature 170-175℃, third stage temperature 160-165℃, and mold temperature 120-140℃.

12. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The catalytic degreasing process conditions in step S5 are as follows: using 98% fuming nitric acid as a catalyst and nitrogen as a protective gas with a flow rate of 40-50 L / min, catalytic degreasing temperature of 110-140℃, nitric acid feed rate of 2-3 g / min, and terminating the degreasing process when the product weight loss rate reaches 7.00%.

13. The method for preparing 1J50 alloy based on metal injection molding according to claim 1, characterized in that, The sintering process conditions in step S6 are as follows: sintering temperature 1370-1380℃, holding time 120-150 minutes, and rapid cooling to room temperature after furnace cooling to 900℃.